Design, synthesis and antitubercular activity of pyrazole and benzo[d]imidazole clubbed dihydroimidazo[1,2-a]pyrimidinones (Indian Journal of Chemistry (IJC), 2023)
The discovery and development of new pharmaceutically active drugs by medicinal chemists is being impeded by the emerging issue of antimicrobial resistance. It triggered the urgent necessity for the generation of new medicinally active compounds. In addition, novel dihydroimidazo[1,2-a]pyrimidinone containing clubbed pyrazole and benzo[d]imidazole derivatives (5a-5o) were developed, synthesized, and tested for their antitubercular efficacy. IR, 1H NMR, 13C NMR, and mass spectroscopy were among the analytical methods used to establish structures of the novel compounds'. The Mycobacterium TB H37Rv strain was used in the antitubercular screening. The most effective derivatives (5c and 5h) against the tested strain had MIC values of 50 µg/mL. The MIC values of the further derivatives 5a, 5b, 5e, 5f, 5g, 5i, and 5l ranged from 62.5 to 125 µg/mL.